Serotonergic control of feeding microstructure in Drosophila - Banu, Ayesha; Gowda, Swetha B. M.; Salim, Safa; Mohammad, Farhan (Frontiers in Behavioral Neuroscience, 2023)
To survive, animals maintain energy homeostasis by seeking out food. Compared to freely feeding animals, food-deprived animals may choose different strategies to balance both energy and nutrition demands, per the metabolic state of the animal. Serotonin mediates internal states, modifies existing neural circuits, and regulates animal feeding behavior, including in humans and fruit flies. However, an in-depth study on the neuromodulatory effects of serotonin on feeding microstructure has been held back for several technical reasons. Firstly, most feeding assays lack the precision of manipulating neuronal activity only when animals start feeding, which does not separate neuronal effects on feeding from foraging and locomotion. Secondly, despite the availability of optogenetic tools, feeding in adult fruit flies has primarily been studied using thermogenetic systems, which are confounded with heat. Thirdly, most feeding assays have used food intake as a measurement, which has a low temporal resolution to dissect feeding at the microstructure level. To circumvent these problems, we utilized OptoPAD assay, which provides the precision of optogenetics to control neural activity contingent on the ongoing feeding behavior. We show that manipulating the serotonin circuit optogenetically affects multiple feeding parameters state-dependently. Food-deprived flies with optogenetically activated and suppressed serotonin systems feed with shorter and longer sip durations and longer and shorter inter-sip intervals, respectively. We further show that serotonin enhances and suppresses sip durations via 5-HT1B and 5-HT7 receptors, respectively.